Modeling the Midlatitude Ionosphere Storm‐Enhanced Density Distribution With a Data Assimilation Model. Issue 10 (10th October 2018) - Gardner, L. C.; Schunk, R. W.; Scherliess, L.; Eccles, V.; Basu, S.; Valladeres, C.
Abstract: The Utah State University Global Assimilation of Ionospheric Measurements‐Gauss Markov model has been used to investigate the distribution of ionospheric plasma during storm times over the continental United States. Storm periods dramatically increase the effects of space weather on the ionosphere and upper atmosphere, leading to impacts on over‐the‐horizon radars, Global Positioning System location determination, spacecraft charging, power grid overloads, and disruption of the Federal Aviation Administration Wide Area Augmentation System to name a few. Four storm periods were investigated where strong storm‐enhanced densities (SEDs) were present: two strong, October 2003 and November 2003, and two moderate, August 2010 and August 2011. It was found that a fundamental difference in the SED formation exists between the strong and moderate storms. For the strong storms, the SED was formed from the plasma in the northern equatorial anomaly crest, with the plasma in the SED channel lifting the closer it came to the high latitudes. For the moderate storms, the SED appeared to be unconnected to the northern anomaly crest but was rather produced locally in the SED channel, along with no corresponding increase in layer height associated with the SED evident in the model. Plain Language Summary: Plasma distributions in the Ionosphere have an impact on communication and geolocation. Storm‐enhanced densities tend to form over midlatitude regions, such as the continental United States. These enhancements tend to disrupt signals such as high‐frequency communications, used by hobbyists and emergency personnel, and geolocation signals, used by airlines, Global Positioning System units, and cell phones. In order to limit the impacts of these disruptions, we need to understand how and why these disruptions form. We looked into the formation of these enhancements by using a data driven model to reproduce periods when they occur. Key Points: Fundamental difference between strong and moderate storm SED formation exists Strong geomagnetic storms form SEDs connected to the Appleton anomaly crests with elevated channel heights Medium geomagnetic storms form SEDs unconnected to the Appleton anomaly crests with unchanged channel heights